Alcohol- and drug-related consequences across latent classes of substance use among American Indian adolescents. (February 2021) - Schick, Melissa R.; Goldstein, Silvi C.; Nalven, Tessa; Spillane, Nichea S.
Highlights: Nearly one-third of adolescents reported any past month substance use. Adolescents had experienced an average of 2–3 substance-related consequences. Use of a greater number of substances was associated with greater consequences. Abstract: Introduction: Substance use among American Indian (AI) adolescents is a significant public health concern, as they report greater health disparities related to substance use compared to other racial/ethnic groups. The present study examines differences across classes of substance use behaviors regarding alcohol- and drug-related consequences. Methods: The current study was a secondary analysis of the dataset used by Stanley and Swaim (2018). AI adolescents ( n  = 3498, 47.8% female, Mage  = 14.8) completed a survey including substance use and related consequences. Protocols were approved by institutional IRB, tribal authority, school boards, and parental consent/child assent were obtained. Results: In line with Stanley and Swaim (2018), we identified four classes of substance use: no past month substance use; marijuana and cigarette use only; alcohol, marijuana, and cigarette use only; and polysubstance use. Cross-class comparisons revealed that adolescents in classes characterized by the use of a greater number of substances also reported experiencing greater alcohol- and drug-related consequences with one exception: the class characterized by marijuana and cigarette use reported greater drug-related consequences compared to the class characterized by alcohol, marijuana, and cigarette use. Conclusions: AI adolescents who engage in the use of multiple substances should be provided with psychoeducation around the increased risk of associated negative consequences. Given the health disparity experienced by AI adolescents, interventions to alleviate the burden of negative consequences are necessary.